The digitalisation of central bank money: China advances while Europe hesitates - Hanns Günther Hilpert; Paweł Tokarski (Stiftung Wissenschaft und Politik (SWP), 2024)
The number of digital currencies has increased significantly in recent years. So-called central bank digital currencies (CBDCs), created by central banks, are at the forefront of this development. Combining the advantages of an electronic means of payment - namely the speed and efficiency of transactions - with the stability and confidence that central banks enjoy, CBDCs will surely have a significant influence on the development of international payment systems in the coming years. Work on this topic has accelerated significantly in many parts of the world following the imposition of sanctions against Russia by the G7. The European Union (EU) and China are also engaged in planning and shaping their own CBDCs, but there are significant differences in the motivations, pace of progress and ambitions associated with these projects.
Keywords: 320; Central Bank; money; digitalisation; digital currencies; central bank digital currencies (CBDCs); sanctions against Russia; G7; European Union (EU); China; eurozone; blockchain technologies; People's Bank of China (PBoC); e-CNY; European Central Bank (ECB)